Participatory democracy in an age of inequality - Rod Dacombe; Phil Parvin (2021)
This article introduces this special issue on Participatory Democracy and Inequality, identifying both the primary claims made by the modern iteration of participatory democracy, as well as the main challenges faced by participatory democrats, by drawing on a range of literature, both empirical and theoretical. Despite these challenges, it finds cause for optimism, based on the trajectory of recent research on participatory democracy, and suggests there might be a number of potential means of addressing the problems raised by democratic inequality.